The rice endophytic bacterium Bacillus velezensis LS123N provides protection against multiple pathogens and enhances rice resistance to wind with increase in yield - Chi-Kuan Tu; Wen-Di Huang; Pei-Han Wang; Wei-Lun Lin; Hong-Yue Chen; Sheng-Tsz Rau; Tsu-Cheng Chang; Li-Sen Young; Chih-Li Wang; Miin-Huey Lee (Biological Control)
Rice (Oryza sativa) is a globally important staple food, but its production was influenced by various biotic and abiotic stresses. This study involved screening endophytic bacterial strains for their antagonistic activities and control efficacy against multiple rice pathogens in planta assays. Subsequent greenhouse investigations identified Bacillus velezensis LS123N as the most promising strain for effectively controlling various rice diseases, including bacterial blight, rice blast, bakanae disease, Pythium disease, and brown spot disease. Field trials further demonstrated that LS123N significantly reduced naturally occurring brown spot disease caused by Bipolaris oryzae in both seedlings and mature rice plants, and increased rice yields. For disease control against bacterial blight, Pythium disease, and brown spot, only a single treatment during seed germination resulted in significant disease control efficacy. The application of LS123N during seed germination aligns with common rice cultivation practices. Additionally, LS123N exhibited the capacity to improve rice resistance to wind stress and enhance rice growth during the seedling stage. Endophytic colonization of LS123N was evidenced from seed to mature rice plants after seed treatment. Interestingly, the expression of many rice defense genes was suppressed within 48 h of the LS123N introduction. In vitro assays showed that LS123N inhibited spore germination and normal growth of germ tubes of B. oryzae, produced multiple hydrolases, siderophores, and IAA, and had the ability to solubilize phosphorus compounds. In summary, these results indicate that B. velezensis LS123N is a promising biocontrol agent and has the potential to be developed into a biofungicide, biofertilizer, and biostimulator.